2021
DOI: 10.1080/15538362.2021.1932692
|View full text |Cite
|
Sign up to set email alerts
|

Does socioeconomic status affect fruit and vegetable intake? Evidence from a cross-sectional analysis of the RaNCD Cohort

Abstract: The purpose of this study is to investigate socioeconomic inequality in fruit and vegetable (F&V) intake and contributing factors. Data of 9981 participants from the recruitment phase of Ravansar Non-Communicable Diseases (RaNCD) cohort study were included in the final analysis. The concentration index was calculated to measure the inequality. The prevalence of adequate F&V intake was 55.8% and concentration index was 0.178, indicating that more people in the higher SES group are consuming enough F&V. Place of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
(35 reference statements)
3
5
1
Order By: Relevance
“…Our results are also consistent with previous studies that showed strong relationships of fruit and vegetable intake with socioeconomic factors or other lifestyle habits (Amini et al, 2021;De Irala-Estévez et al, 2000;Estaquio et al, 2008) which may confound the association with SRH. Low education or unemployment, for example, can lead to lower fruit and vegetable intake due to financial constraints, while these factors are also often predictors of low SRH (Lindholm et al, 2001).…”
Section: Interpretation Of Findingssupporting
confidence: 93%
“…Our results are also consistent with previous studies that showed strong relationships of fruit and vegetable intake with socioeconomic factors or other lifestyle habits (Amini et al, 2021;De Irala-Estévez et al, 2000;Estaquio et al, 2008) which may confound the association with SRH. Low education or unemployment, for example, can lead to lower fruit and vegetable intake due to financial constraints, while these factors are also often predictors of low SRH (Lindholm et al, 2001).…”
Section: Interpretation Of Findingssupporting
confidence: 93%
“…In the present study, no third-order interactions were found, indicating that the effect of ending the program did not differ according to sex or parental education, which means that there was no difference between boys and girls, or between socioeconomic groups (based on parental education) in this sample. Thus, the findings do not confirm the results of studies showing that free school meals equalize social inequality [15][16][17], but also do not support the studies that show higher FV intake in high socioeconomic groups [12,13].…”
Section: Discussioncontrasting
confidence: 95%
“…Several studies have indicated socioeconomic differences in dietary habits, including FV intake, as people with higher education usually eat more FV than those with lower education [12,13]. In addition, health promotion measures are often more effective among families with a high socioeconomic background, which may contribute to an increase rather than a decrease in health disparities among different socioeconomic groups [14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the highest household welfare quintiles contributed to more than 40 % of the inequalities in fruit and vegetable consumption between 2014 and 2019 (with a decrease of 9•1 percentage points in 2019), while an urban place of residence contributed 10 % of the inequalities in 2014 and 17•3 % in 2019. These results are similar to those reported in previous studies conducted in Iran and India (36) . The contribution of inequalities in the highest welfare quintiles can be attributed to household purchasing power, in which the cost of two servings of fruit and three servings of vegetables per d represents more than 50 % of household income in low-income countries, which may reflect the unaffordability of lower-income households to purchase fruit and vegetables (45) .…”
Section: Discussionsupporting
confidence: 93%
“…We found a concentration of adequate fruit and vegetable consumption per day among people with a higher wealth index. Similar findings have been described in other studies conducted worldwide (24,(34)(35)(36)(37) that report that more people with a high socioeconomic level have an adequate consumption of fruits and vegetables compared to the poorest. An explanation for this could be that people living in lower-income households make less healthy and lower quality food purchases and have less access to fruits and vegetables due to the high cost of this type of food (38) .…”
Section: Discussionsupporting
confidence: 90%